2016
DOI: 10.1002/malq.201600051
|View full text |Cite
|
Sign up to set email alerts
|

Questions on generalised Baire spaces

Abstract: We provide a list of open problems in the research area of generalised Baire spaces, compiled with the help of the participants of two workshops held in Amsterdam (2014) and Hamburg (2015).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 50 publications
(105 reference statements)
1
25
0
Order By: Relevance
“…In case κ is strongly inaccessible in the ground model -and weakly inaccessible in the extension -the consistency of cov(M κ ) < d κ ( = * ) answers a question of Matet and Shelah [MS,Section 4] (see also [KLLS,Question 3.8,part 2]).…”
Section: Generalized Hechler Forcingmentioning
confidence: 99%
See 1 more Smart Citation
“…In case κ is strongly inaccessible in the ground model -and weakly inaccessible in the extension -the consistency of cov(M κ ) < d κ ( = * ) answers a question of Matet and Shelah [MS,Section 4] (see also [KLLS,Question 3.8,part 2]).…”
Section: Generalized Hechler Forcingmentioning
confidence: 99%
“…Question 22. (Matet,Shelah [MS,Section 4], see also [KLLS,Question 3.8, part 1]) Is it consistent that κ is a successor cardinal and d κ ( = * ) < d κ ?…”
Section: (Landvermentioning
confidence: 99%
“…This paper is concerned with forcings consisting of uncountable trees. In particular we focus on some issues about pure decision and Cohen κ-reals, attacking some points raised in [11,Question 3.20]. The main part of the paper is centered around the investigation of amoeba forcings, and more generally, the effects of adding uncountable generic trees over models of ZFC.…”
Section: Introductionmentioning
confidence: 99%
“…We remark that this reaserch field has largely spread out in the last years among set theorists. In particular, the problems analysed in this paper are part of those collected in [11], which is the output of a series of workshops which took place in Amsterdam (November 2014), Hamburg (September 2015) and Bonn (September 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we would like to draw attention both on the sometimes surprising results emerging in this area, and on the remarkably wide variety of open problems and lines for further research that are consequently revealed. Recent work, by various people, on generalized Baire spaces and related set-theoretic issues (see, for instance, Friedman, Khomskii and Kulikov [15] and Khomskii, Laguzzi, Löwe and Sharankou [23]) should be thought as complementary in this direction, possibly with important underlying connections waiting to surface.…”
Section: Introductionmentioning
confidence: 99%